2008
DOI: 10.1136/bmj.a180
|View full text |Cite
|
Sign up to set email alerts
|

Bullous pemphigoid and pemphigus vulgaris--incidence and mortality in the UK: population based cohort study

Abstract: Bullous pemphigoid and pemphigus vulgaris-incidence and mortality in the UK: population based cohort study Design Retrospective historical cohort study.Setting Computerised medical records from the health improvement network, a large population based UK general practice database.Participants Patients with pemphigus vulgaris and bullous pemphigoid diagnostic codes and age, sex, and practice matched controls.Main outcome measures Incidence and mortality compared with the control population by calendar period, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

50
535
10
59

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 566 publications
(654 citation statements)
references
References 20 publications
50
535
10
59
Order By: Relevance
“…It is the most common autoimmune bullous disease in Western Europe and North America (6), and probably in most countries of the world (5), which aff ects mostly the elderly (7). Th e reported incidence varies greatly among diff erent countries: from 0.25/100.000 inhabitants per year in Romania (6), through 2.2/100 000 inhabitants in France or 2.4/100.000 persons per year in the United States (8), to 4.3/100 000 persons per year in the United Kingdom (9). Th e incidence appears to be increasing in the last two decades (8,9), which may be attributed to greater proportion of older persons in the population (9), or to increasing incidence of neurological diseases, and use of certain medications which are implicated as risk factors for development of BP (10).…”
Section: Discussionmentioning
confidence: 99%
“…It is the most common autoimmune bullous disease in Western Europe and North America (6), and probably in most countries of the world (5), which aff ects mostly the elderly (7). Th e reported incidence varies greatly among diff erent countries: from 0.25/100.000 inhabitants per year in Romania (6), through 2.2/100 000 inhabitants in France or 2.4/100.000 persons per year in the United States (8), to 4.3/100 000 persons per year in the United Kingdom (9). Th e incidence appears to be increasing in the last two decades (8,9), which may be attributed to greater proportion of older persons in the population (9), or to increasing incidence of neurological diseases, and use of certain medications which are implicated as risk factors for development of BP (10).…”
Section: Discussionmentioning
confidence: 99%
“…In experimental autoimmune encephalomyelitis, GM-CSF is required to sustain neuroinflammation via myeloid cells infiltrating the CNS (14). Given the rising incidence of autoimmune diseases in general and autoimmune bullous dermatoses specifically (53,54), the so far limited therapeutic options (55,56), and the high morbidity and mortality of the patients (54), there is a clear need for novel treatment strategies. In several autoimmune diseases, such as rheumatoid arthritis, inhibition of cytokines or growth factors has dramatically improved the management of these conditions (57)(58)(59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…Lan--gan et al in 2008, mentioned that mortality rate of pemphigus may range as 4.8% and 54%. 10 Oral mu--cosal manifestation (fluid filled blisters or bullous, erosions) was observed in all the patients, and most prevalent oral site was buc--cal mucosa (92.85%), which is fol--lowed by Soft palate (71.42%), lower lip (42.85%), tongue (35.71%), labial mucosa (28.57%), floor of mouth (21.42%), upper lip (14.28%), gingival (14.28%), and hard palate (7.14%). 78.57% (11 out of 14) patients had reported that, oral mucosal manifestation as a primary site of disease pro--cess.…”
Section: Discussionmentioning
confidence: 99%